2019
DOI: 10.1002/uog.20268
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound probes are human papillomavirus‐free following low‐level disinfection: cross‐sectional multicenter survey

Abstract: Objectives To assess the frequency of detection of high‐risk human papillomavirus (hrHPV) on transvaginal ultrasound (TVS) probes and keyboards and evaluate operator compliance with national recommendations for prevention of cross‐infection during TVS. Methods This was a multicenter observational survey involving 46 public and private centers, in the Paris region of France, in which at least five consecutive TVS examinations were performed per day. We audited 676 TVS procedures. We recorded preventive hygien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The studies by both Lucet et al and Benet et al contradict these studies [36,37]. The Lucet group audited 676 TV transducers to screen for HR-HPV and found no evidence of contamination post-cover removal and LLD [36]. Benet et al concluded from a retrospective cohort of 50,244 patients tested for HIV and 105,955 patients tested for HCV that exposure to TV, TR or TOE transducers in the 12 months preceding testing was not associated with an increased risk of infection [37].…”
Section: The Use Of Probe Covers and Low-level Disinfection For Endoc...mentioning
confidence: 89%
See 2 more Smart Citations
“…The studies by both Lucet et al and Benet et al contradict these studies [36,37]. The Lucet group audited 676 TV transducers to screen for HR-HPV and found no evidence of contamination post-cover removal and LLD [36]. Benet et al concluded from a retrospective cohort of 50,244 patients tested for HIV and 105,955 patients tested for HCV that exposure to TV, TR or TOE transducers in the 12 months preceding testing was not associated with an increased risk of infection [37].…”
Section: The Use Of Probe Covers and Low-level Disinfection For Endoc...mentioning
confidence: 89%
“…The studies by both Lucet et al and Benet et al contradict these studies [36,37]. The Lucet group audited 676 TV transducers to screen for HR-HPV and found no evidence of contamination post-cover removal and LLD [36].…”
Section: The Use Of Probe Covers and Low-level Disinfection For Endoc...mentioning
confidence: 98%
See 1 more Smart Citation
“…Chlorine dioxide has well‐documented bactericidal, mycobacterial and sporicidal properties and has become a popular HLD method 20 , 37 . Although studies have reported complete decontamination following the use of chlorine dioxide wipes, recent work suggests the ongoing presence of bacterial growth on some of the probes evaluated 18 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the optimal method to disinfect these transducers need to consider other pathogens aside from SARS-CoV-2 [7,32]. Although most commercially available disinfecting wipes (LLD) cannot eliminate all microorganisms; they are still effective against common viral pathogens such as human papillomavirus (HPV), human immunodeficiency virus (HIV), and coronaviruses [57].…”
Section: Sanitization Of Ultrasound Equipmentmentioning
confidence: 99%